Performance comparison of indoor navigation and obstacle avoidance methods for low-cost implementation in wheelchairs - Ashwathnarayan, Satish Bhogannahalli; Arsa, Deekshitha; Yerriyuru Narasimhaiah, Sharath Kumar; Anchan, Shreyas; Prasath, Giri (International Journal of Reconfigurable and Embedded Systems (IJRES), 2025)
Wheelchairs are a huge support for the movement of people who have disabilities. The wheelchairs that were traditionally moved using manual effort have given way to powered and smart wheelchairs with various controlling methods. When powered wheelchairs are used indoors, navigation and avoiding obstacles become challenging and tricky for a disabled user. To address these challenges there have been implementations of expensive and high-end systems to make the wheelchair move autonomously but as a result such a wheelchair is not economically viable for many users. Thus, there is a need for an alternative low cost method for users to be able to navigate and move in an indoor environment. The paper reviews low-cost methods for implementing indoor navigation systems, weighing their performances to validate if these methods can be used as a viable alternative to the high-cost systems for autonomous navigation in an indoor environment.